Ecoformação artística : percurso coletivo de aprendizagens - Silva, Rosana Gonçalves da (2019)
The text presents notions about Artistic Eco-formation, considering some of elements of a research titled AnElos (The study) Eco-pedagogical Expectations between Complexity and the Earth Charter: creative inventions in daily school. The path to collective learning comprised an interactive educational process based on Poetic Language and in Human Ecology, in Complex Thinking and the principles of the Earth Charter, coordinating the routine of individuals subject to